2008
DOI: 10.1088/0957-0233/20/2/025304
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic signatures of broadband optical spectra for liquor discrimination

Abstract: Methods based upon chromatic analysis are described for quantifying broadband optical absorption spectra in discriminating between different types of liquors. The absorption spectra are quantified by three chromaticity coordinates, which can be represented by two points, one on each of two chromatic diagrams. Various types of liquors may then be distinguished on such chromatic maps and groups of similar samples conveniently identified. Examples of the deployment of the approach are given for distinguishing bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…10,24,30 For whiskies, it was reported that absorbance patterns could be established for specific Scotch brands; therefore any variation out of range of the established values could signify an adulteration. For the discrimination among tequilas, Barbosa-Garcia et al, 25 and Jones et al, 26 used the measured spectra with chemometrics calculations and methods based upon chromatic analysis of the broadband, respectively. However, these studies were conducted without the aid of chromatography to support the analysis.…”
Section: Spectral Characteristics Of Tequila and Mezcal Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…10,24,30 For whiskies, it was reported that absorbance patterns could be established for specific Scotch brands; therefore any variation out of range of the established values could signify an adulteration. For the discrimination among tequilas, Barbosa-Garcia et al, 25 and Jones et al, 26 used the measured spectra with chemometrics calculations and methods based upon chromatic analysis of the broadband, respectively. However, these studies were conducted without the aid of chromatography to support the analysis.…”
Section: Spectral Characteristics Of Tequila and Mezcal Samplesmentioning
confidence: 99%
“…For the case of tequila, chromatic analysis and chemometrics tools have been applied to FT-IR and UV-Vis absorption spectra to discriminate between 100% agave and mixed tequilas as well as among tequilas from different brands. [25][26][27][28] As of the present time, however, no study has been reported which uses UV absorption spectrophotometry to discriminate tequilas from mezcals, nor which attempts to identify the individual chemical components responsible for the UV spectral behavior of these spirits by using RP-HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…The outputs were also processed by CIE (Commission Internationale de l'Eclairage) chromaticity coordinates (x, y), Saturation (S) and Hue (H) algorithms of color science [21][22][23] for comparison. Hence, CR and other chromatic parameters were applied to DTE24 #2 and DTE25 oils sampled a steel factory (POSCO, Korea); the results presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The ultraviolet spectral range was successfully exploited by a commercially-available instrument which is capable of verifying the authenticity of commercial brands [10][11], while chromatic analyses extending to the visible were also experimented [12][13]. More recently, the mid-infrared spectral range provided a means for detecting counterfeit samples [14].…”
Section: Whisky and Brand Protectionmentioning
confidence: 99%